“APOTIK” : APLIKASI PROBIOTIK SEBAGAI ALTERNATIF DALAM MEMPERCEPAT PERTUMBUHAN PROSES BUDIDAYA UDANG GALAH DI DESA PADANG KERTA KARANGASEM - Ida Ayu Manuaba Sudiadnyani; I Ketut Yongki Wiarawan; Ida Ayu Widi Adnyani; Yustinus Victor Rianus Bura; Luh Kadek Budi Martini (Jurnal Bakti Saraswati (JBS): Media Publikasi Penelitian dan Penerapan Ipteks, 2018)
The village of Padang Kerta, Karangasem regency, Bali became the center cultivation of giant prawns. Uniquely, the cultivation of giant prawns this village is not done in permanent ponds but utilize non-productive rice field but most of the farmers in this area still do not know about the use of Probiotics and its benefits in the process of cultivation of giant prawns. Probiotics are living microorganisms that are intentionally introduced into ponds or in feed to provide beneficial effects for shrimp health. PKM-T group took the initiative to continue the results of Probiotics to be applied to other Giant Prawns for the purpose of supporting the process of Giant Prawn Growth and Productivity in Padang Kerta Village, Karangasem. Probiotics can be applied either to water as a culture medium or to feed used, the application of water may use formulations (20 liters of water + 1 l of molasses + 1 lt probiotic) while on feed 1 weft sack (30 kg + 1 lt molase + 1 lt probiotics) that have been fermented for ± 3 to 4 days or adjusted to the probiotic packed dose concerned principally there is molasses (molasses + feed + probiotics or bats (Lactobacillus + saccaromyces)). Based on the results of the process of shrimp culture business group PKM-K Mahasaraswati Denpasar University who successfully pass PIMNAS (National Student Scientific Week) Year 2017 with the title "Cultivation of giant prawns In Subak Peladung, Tempek Gerenjeng, Padang Kerta Village, Karangasem District, Karangasem Regency" which is chaired by Ida Ayu Manuaba Sudiadnyani able to produce high quality giant prawns products with a very good cultivation process with assisted use of Probiotics. With 100kg giant prawns or 5000 heads with Size S 50 tail / kg, (1 weigh 20 g), sell Size M with stuffing 30 head / kg with price Rp. 95.000 - Rp. 105,000. (1 tail weight-a 33 g) .With a shrinkage of 5% or dead from Size S 250 tail, or living 4750. With last embedded capital for 4 months is Rp. 11.498.000tim PKM-K obtained Net Profit Rp. 4,792,000 (44%).